1999
DOI: 10.1021/ma9810114
|View full text |Cite
|
Sign up to set email alerts
|

Structure Development during Crystallization of Homogeneous Copolymers of Ethene and 1-Octene:  Time-Resolved Synchrotron X-ray and SALS Measurements

Abstract: Crystallization kinetics in a homogeneous copolymer of ethene and 1-octene with appended long chain branches has been investigated in real time by means of time-resolved light scattering under H V (cross-polarized) and V V (parallel-polarized) optical alignments using a CCD camera system, simultaneous small angle-X-ray and wide angle X-ray measurements using synchrotron radiation and differential scanning calorimetry (DSC). The data show that in the case of crystallization at large supercooling, a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 32 publications
(56 reference statements)
8
75
0
Order By: Relevance
“…12 It has also been reported that a small amount of chain branches appears to hinder the isothermal thickening process in polyethylene. 25 The argument of isothermal lamellar thickening is also consistent with the decrease in amorphous layer thickness with time [ Figs. 2(a) and (b)].…”
Section: Effect Of Miscible Polymer Diluents On Lamellar Morphologysupporting
confidence: 65%
See 1 more Smart Citation
“…12 It has also been reported that a small amount of chain branches appears to hinder the isothermal thickening process in polyethylene. 25 The argument of isothermal lamellar thickening is also consistent with the decrease in amorphous layer thickness with time [ Figs. 2(a) and (b)].…”
Section: Effect Of Miscible Polymer Diluents On Lamellar Morphologysupporting
confidence: 65%
“…The decrease in L at long times has recently been reported by time-resolved SAXS techniques in many polymers: poly(ethylene terephthalate) (PET), 20,21 poly(aryletheretherketone) (PEEK), 11,22,23 isotatic polypropylene (iPP), 24 and ethylene 1-octene copolymer. 25 This behavior again can be attributed to the secondary crystallization process (after spherulites impinge) through the lamellar stack-insertion mechanism. It is noted that the change in la in the above systems is relatively small during prolonged annealing; we thus believe that the lamellar stack insertion mechanism may be favored at this stage.…”
Section: Effect Of Miscible Polymer Diluents On Lamellar Morphologymentioning
confidence: 95%
“…The crystallinity at the gel point, X c , was found to be about 3% at slow crystallization and slightly higher at increased rate of crystallization (higher undercooling, ∆T). The observations of Schwittay et al 1 were confirmed and, possibly, explained by recent experiments of Akpalu et al 6 who, for a crystallizing polyethylene (PE), found that spherulites reach their full size after very short times of crystallization and at very low crystallinity. This similarity in behavior is quite surprising in view of the very different crystal habit in PE and iPP.…”
Section: Introductionmentioning
confidence: 69%
“…There is considerable experimental evidence [9][10][11][12][13][14][15] for density fluctuations at very early times of crystallization before the full crystallographic features can be detected. What are the molecular origins of structural development in the primordial stage of polymer crystallization?…”
Section: B Nucleation In the Very Early Stagementioning
confidence: 99%